MEDIA MASSA DAN DEHUMANISASI - Nurudin, Nurudin (Jurnal Bestari, 2008)
Mass media has enormous power in cotrolling people's belief. Its ups and downs are truly directed by the media. In can be said that media take part in the developed society, however, media also take part in the deterioration of the society. This writing talks about the effects of mass media in leading to the dehumanization. This text aims at examining what caused dehumanization and what media should perform interm of turn dehumanization down.